2018
DOI: 10.1136/openhrt-2017-000743
|View full text |Cite
|
Sign up to set email alerts
|

SuPAR predicts postoperative complications and mortality in patients with asymptomatic aortic stenosis

Abstract: BackgroundWe evaluated whether early measurement of soluble urokinase plasminogen activator receptor (suPAR) could predict future risk of postoperative complications in initially asymptomatic patients with mild-moderate aortic stenosis (AS) undergoing aortic valve replacement (AVR) surgery.MethodsBaseline plasma suPAR levels were available in 411 patients who underwent AVR surgery during follow-up in the Simvastatin and Ezetimibe in Aortic Stenosis (SEAS) study. Cox analyses were used to evaluate suPAR in rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…The investigators reported an association of elevated suPAR with adverse cardiovascular outcomes in non-severe AS. Preoperative plasma suPAR levels were measured in 411 members of the same cohort requiring aortic valve replacement surgery [ 43 ]. All patients were asymptomatic with mild to moderate AS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigators reported an association of elevated suPAR with adverse cardiovascular outcomes in non-severe AS. Preoperative plasma suPAR levels were measured in 411 members of the same cohort requiring aortic valve replacement surgery [ 43 ]. All patients were asymptomatic with mild to moderate AS.…”
Section: Resultsmentioning
confidence: 99%
“…The prognostic value of suPAR has been investigated in patients with cardiac diseases who underwent invasive procedures such as in those who had a primary PCI after the first MI [ 12 ]. Its role as a marker of inflammation for patients after a TAVI procedure [ 45 ] has been evaluated, as has its predictive value for postoperative complications in patients who had an aortic valve replacement [ 43 ] and its prognostic utility, its temporal course, and its relation to CRP in patients with ST-segment elevation MI who had a PCI [ 10 ]. In all the aforementioned studies elevated suPAR levels were indicative of increased underlying inflammatory stimuli and were characterized by a high predictive value for major cardiac events and complications after invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,[36][37][38][39] To the extent of the authors' knowledge, only one study has investigated suPAR's prognostic ability in relation to cardiac surgery and demonstrated that increasing preoperative levels of suPAR were associated with higher risk of postoperative complications and 30-day mortality. 20 However, the study exclusively comprised patients with aortic stenosis for aortic valve replacement. 20 Of note, suPAR levels were almost identical to those of the present study and, likewise, no benefit was gained by adding suPAR to Euro-SCORE II.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] However, the relationship between the biomarkers and outcome after cardiac surgery only recently has been explored. [15][16][17][18][19][20] Previous studies showed associations between elevated preoperative hsCRP values and subsequent development of cardiovascular events as well as increased short-, mid-, and long-term mortality in isolated coronary artery bypass grafting (CABG) procedure cohorts. [15][16][17][18][19] A single study explored the association between preoperative suPAR levels and a combined endpoint of postoperative complications and the 30-day mortality rate after cardiac surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation